PENGUJIAN KENDARAAN BERMOTOR UNTUK MEWUJUDKAN KESELAMATAN BERLALU LINTAS DI KOTA DENPASAR - Putu Lantika Oka Permadhi (University of Udayana, 2017)
Transportation plays an important role in supporting, improving and enhancing the economic development both regionally and nationally. The need for services is increasing traffic, limiting the number of motor vehicles as much growing from year to year in Denpasar City causes unbalance between the number of vehicles available with the road infrastructure are available and also increase the traffic accident per year. Accidents in the road are usually caused by motor vehicles. In this case largely due to technical factors and not roadworthy. The issues examined are how is the implementation of the motor vehicle feasibility test in Denpasar City and whether is the implementation of vehicle testing already able to realize the safety of traffic in Denpasar City. The research was classified into empirical legal research of the descriptive analysis research using primary and secondary data. Transportasi memainkan peran penting dalam mendukung, memperbaiki dan meningkatkan pembangunan ekonomi baik di tingkat regional maupun nasional. Kebutuhan akan layanan lalu lintas semakin meningkat, jumlah kendaraan bermotor bertambah dari tahun ke tahun di Kota Denpasar sehingga menyebabkan ketidakseimbangan antara jumlah kendaraan yang dengan infrastruktur jalan dan juga meningkatkan kecelakaan lalu lintas per tahun. Kecelakaan yang terjadi di jalan biasanya disebabkan oleh kendaraan bermotor, dalam hal ini sebagian besar dikarenakan dari faktor teknis dan tidak layak jalan. Permasalahan yang diteliti adalah Bagaimana pelaksanaan uji kelayakan kendaraan bermotor di Kota Denpasar dan Apakah pelaksanaan pengujian kendaraan bermotor sudah dapat mewujudkan keselamatan berlalu lintas di Kota Denpasar. Penelitian ini diklasifikasikan ke dalam penelitian hukum empiris dari penelitian analisis deskriptif dengan menggunakan data primer dan data sekunder.